Cash Flow Management Studies: A Bibliometric Examination of Global Research - Loso Judijanto (Westscience Press, 2026)
This study aims to map and analyze the intellectual structure, thematic development, and evolution of cash flow management research through a bibliometric approach. Using a dataset of global scholarly publications indexed in Scopus, this study applies bibliometric techniques, including co-occurrence analysis, overlay visualization, and density mapping, to identify key themes, research clusters, and emerging trends. The results reveal that cash flow management research is anchored in core financial topics such as investment analysis, risk management, and decision making, which form the central structure of the field. Over time, the literature has expanded beyond technical and project-based applications toward broader strategic perspectives, including corporate governance, sustainability, and financial management. The findings also indicate a growing integration of environmental and economic considerations, reflecting a shift toward long-term value creation and responsible financial practices. This study contributes by providing a comprehensive overview of the knowledge landscape and identifying future research directions, particularly in integrating interdisciplinary approaches within cash flow management studies.